Non-contiguous metathesis in Spoken Iraqi Arabic: An optimality-theoretic study - Al-Ahmed, Tuqa Safaa Aldeen Salih; Rashid, Balqis I. G. (Edelweiss Applied Science and Technology, 2025)
This study investigates the phonological process of non-contiguous metathesis in spoken Iraqi Arabic (henceforth SIA) within the framework of Optimality Theory (henceforth OT). The study aims to test OT’s capability to account for non-contiguous metathesis in SIA and to identify the triggers behind this phonological process. Following the presentation of SIA data, an OT analysis is developed. The results demonstrate that OT effectively describes and explains all instances of non-contiguous metathesis identified in the study. Regarding the triggers for this process, the analysis identifies four distinct patterns of non-contiguous metathesis in SIA, each driven by specific constraints: the first pattern is triggered by sonority-related constraints, the second by feature agreement constraints, the third by sequential constraints, and the fourth by alignment constraints. These findings indicate that, in SIA, resolving marked structures of the language takes precedence over preserving the linear order of segments.